Method for producing menthol particles stabilized against caking and storage-stable menthol particles and uses thereof

A method involving storage and mechanical energy application stabilizes menthol particles against caking, addressing the inefficiencies of existing methods and ensuring long-term free-flowing properties for use in consumer products.

JP7608326B2Active Publication Date: 2025-01-06BASF SE
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
JP2021507850
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2018-08-16
Filing Date
2019-08-14
Publication Date
2025-01-06
Estimated Expiration
2039-08-14

AI Technical Summary

Technical Problem

Existing methods for producing menthol particles result in caking and agglomeration, leading to undesirable processing costs and inefficiencies, particularly when stored over extended periods, and there is a need for a cost-effective method to produce free-flowing menthol particles suitable for various shapes and forms.

Method used

A method involving storage of menthol particles at 0 to 30°C for at least 7 days followed by the application of mechanical energy, such as dropping packaged menthol particles from a height, to stabilize against caking, ensuring they remain free-flowing even after 18 weeks.

Benefits of technology

The method effectively stabilizes menthol particles against caking, maintaining their shape and size, making them suitable for use in household and consumer products, with improved storage stability and reduced caking tendencies.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007608326000001
    Figure 0007608326000001
  • Figure 0007608326000002
    Figure 0007608326000002
  • Figure 0007608326000003
    Figure 0007608326000003
Patent Text Reader

Abstract

The present invention relates to a method for producing menthol particles stabilized against caking, which comprises storing the menthol particles after shaping at a temperature between 0 and 30° C. for at least 7 days, after which a minimum amount of mechanical energy is applied to the menthol particles. The present invention also relates to storage-stable menthol particles and to the use of said menthol particles in all kinds of use and consumption articles. [Selection diagram] None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a method for producing menthol particles stabilized against caking, wherein the menthol particles are stored after shaping at a temperature between 0 and 30° C. for at least 7 days, after which the menthol particles are subjected to a minimal input of mechanical energy. The present invention also relates to storage stable menthol particles and to the use of said menthol particles in all kinds of daily necessities and consumer goods. [Background technology]

[0002] Menthol is a naturally occurring active substance that is widely used in the pharmaceutical, cosmetic and food industries. Menthol has a cooling effect on contact with mucous membranes, especially the oral mucous membrane. In natural sources, such as peppermint oil, menthol exists in the form of four diastereomeric enantiomeric pairs, of which only the main component (-)-menthol or L-menthol has the desired taste and other sensory properties.

[0003] It has been known for some time that L-menthol can solidify in four different crystalline modifications, which have the same chemical composition but different physical properties, as already described in J. Am. Chem. Soc., Vol. 39 (No. 8), 1917, pp. 1515-1525. For example, the melting points of these various modifications are in particular between 33° C. and 43° C., as described, in particular, in Archiv der Pharmazie, Vol. 307 (No. 7), 1974, pp. 497-503. The melting point of the stable alpha modification is therefore 42-43° C.

[0004] Having a melting point of this order means that L-menthol can be provided to intermediate or end users either as a melt, remaining liquid in a heated vessel, or in the form of crystals or other solidified moldings. All solids, like L-menthol, have a melting point only slightly above ambient temperature and generally have a high tendency to caking and agglomerating. However, the processing of such caked materials leads to significant undesirable additional expenditure. If pure L-menthol, i.e. menthol that has not been treated with auxiliaries, such as separating agents, is sold in solid form, the nature of the molding must ensure that the product reaches the intermediate or end user in a free-flowing form.

[0005] Menthol is commercially available in the form of large needle-like crystals, e.g. 0.5-3 cm long and 1-3 mm thick. They are conventionally produced in small quantities from naturally occurring peppermint oil by crystallizing the oil in refrigerators, tubs or vats for several days. These needle-like crystals have good pourability only at short filling heights, but show obvious caking when the usage amount is increased and / or at high temperatures. Moreover, the nature of their production means that they always contain residues of the oil from which they are obtained. The technical expenditure involved in the crystallization, separation and washing of the needles as well as the low space-time yields make such a difficult process unfavourable.

[0006] DE 25 30 481 relates to an apparatus for crystallizing substances, in particular optically active menthol, which forms coarse needle-like and rod-like crystals under crystallization conditions. Crystallization methods carried out batchwise use special stirrers that prevent the crystals from caking in the crystal suspension. The desired product is finally isolated using centrifugation and dried in a dryer.

[0007] US 3,023,253 and US 3,064,311 (Bain) describe flaked L-menthol and a method for producing such flakes by applying a melt of L-menthol to a cooled immersed roller. If desired, the menthol melt can be introduced between a pair of counter-rotating cooled rollers. The film of menthol crystallized on the immersed roller is subjected to a post-treatment consisting of a heat treatment by the introduction of heat and a strengthening by the application of additional menthol. The two post-treatments are carried out simultaneously using an application roller. The flakes so obtained initially have good flowability. However, on prolonged storage, caking occurs.

[0008] The principle of further coarsening of the primary particles by compaction is also described in WO 03 / 101924 (Symrise), which relates to compressed menthol in the form of menthol compacts and to a method for their manufacture. However, attention should be paid here not only to the effect of particle size, but also to the fact that the primary particles must be present in a specific crystal modification. It is possible to obtain compacts by compacting the crystals obtained by crystallization from a solution or by flaking using cooling rollers.

[0009] WO 2008 / 152009 (BASF) describes a process for producing L-menthol in solid form, in particular in the form of flakes, by contacting an L-menthol melt with two spaced apart cooled surfaces, as well as the solid forms of L-menthol obtainable by said process and their use for incorporation into all kinds of household and consumer goods.

[0010] WO2016 / 016154 (Symrise) describes a method for producing a solid coolant in which a pre-abraded melt of a menthol compound, i.e. a melt with a seed crystal, is dripped evenly onto a pre-cooled surface. The menthol particles thus obtained in the form of pellets have a cone and a flat surface and a diameter of about 1 to about 20 mm.

[0011] EP 3 059 009 A1 (Symrise) describes a method for the caking-free storage of solid coolants, where these are packaged in standard packaging having a maximum volume of 25 liters, provided that the packaging is filled to no more than 50% by volume and that the packed contents do not exceed a weight of 10 kg.

[0012] WO2006 / 097427 (Symrise) describes a menthol-containing solid composition comprising or consisting of a solid menthol component and a solid silicon dioxide component.

[0013] WO2007 / 071512 (Symrise) describes spherical menthol particles and a method for producing them, in which a menthol melt is dropped into water.

[0014] WO2016 / 034481 (Sandvik) describes a method and apparatus for producing L-menthol pellets, in which molten droplets of a menthol melt are deposited by a droplet former onto a cooling belt where they solidify. Summary of the Invention [Problem to be solved by the invention]

[0015] In light of the prior art mentioned, the object of the present invention was to provide a method for producing storage-stable menthol particles, and also menthol particles stabilized against caking.The method should be possible to carry out, especially on an industrial scale, with the lowest possible expenditure on equipment and with high throughput, and the obtained menthol particles stabilized against caking should be free-flowing and, in particular, show a minimum tendency to caking over a relatively long period of time.In addition, the method should be possible to carry out especially economically, i.e. cost-effectively.The method should furthermore be suitable for a very wide range of shapes of menthol particles. [Means for solving the problem]

[0016] The present invention relates to a method for producing menthol particles stabilized against caking, comprising storing the menthol particles, after molding, at a temperature of 0-30° C. for at least 7 days, after which the menthol particles are stabilized against caking by the addition of a hydroxypropyl group to the menthol particles. 20 kg of said menthol particles, - packed in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; - the bags are packed in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; - The box is dropped once from a height of 1.0 m onto an inelastic surface with the plane parallel to the sides formed by L(box) and H(box). To provide a method for applying mechanical energy at least as great as that which would be applied if the object were to be subjected to mechanical energy.

[0017] The phenomenon known as caking or agglomeration is probably essentially due to particles combining to form aggregates.Surprisingly, it has been found that the menthol particles obtained using the method of the present invention are stabilized against caking.This means in particular that the number of particles in the aggregates, when stored at 20°C for more than 18 weeks, is reduced more gently than the number of particles in a comparison aggregate that has not been subjected to the method of the present invention.The menthol particles thus obtained are free-flowing even after more than 18 weeks of storage at 20°C, and can therefore be used, for example, directly and without additional energy consumption, for the manufacture of daily necessities and consumer goods, such as cosmetics and pharmaceutical products or foodstuffs and confectionery. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] The method of the invention is characterized by two steps. In the first step, the menthol particles used as starting product of the method of the invention are stored after molding at a temperature between 0 and 30 ° C for at least 7 days. This is followed by a second step of applying mechanical energy to the stored menthol particles. In this step, the menthol particles are subjected to a mechanical energy treatment so that they 20 kg of said menthol particles, - packed in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; - the bags are packed in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; - The box is dropped once from a height of 1.0 m onto an inelastic surface with the plane parallel to the sides formed by L(box) and H(box). The force exerted on the body is at least as great as that exerted on the body by the force of the shock wave.

[0019] Storage after molding can be performed at a temperature of 0 to 30° C., preferably 5 to 25° C., particularly 10 to 23° C., and preferably 12 to 20° C. Storage is for at least 7 days. Storage can be performed, for example, at 20° C. for 10 days, or at 18° C. for 21 days.

[0020] The storage time begins at the end of the shaping of the menthol particles used, which is the point at which the menthol particles used have acquired their desired shape, size and / or size distribution.

[0021] The storage period is not critical, provided that it amounts to 7 days. Storage times of, for example, 14 days, 21 days or even several months, for example 1, 2, 6 or 12 months, or even more than 1 year, are therefore conceivable. Storage is usually at least 7 days and up to 3 months, in particular up to 4 months, in particular up to 6 months.

[0022] The storage conditions other than temperature and the minimum storage period are not critical. Storage can be carried out in conventional packaging units, such as bags, sacks, boxes, drums or combinations thereof. When packaging the menthol particles in a packaging unit, it is advantageous to ensure that the temperature does not fall below the dew point temperature, so that condensation does not form in the packaging unit. It is advantageous if the temperature does not fall below the dew point temperature during storage. Storage is preferably carried out at a relative humidity of less than 65%.

[0023] Ideally, both the storage and the mechanical energy input take place in one and the same packaging unit, such as a box, drum, sack, bag or similar conventional container as described below.

[0024] In one embodiment of the invention, both steps of the method of the invention are carried out in one packaging unit.

[0025] The input of mechanical energy can be provided by a variety of means. 20 kg of said menthol particles, - packed in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; - the bags are packed in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; - The box is dropped once from a height of 1.0 m onto an inelastic surface with the plane parallel to the sides formed by L(box) and H(box). It is important to be able to give at least as much energy as you would receive in such a case.

[0026] The amount of mechanical energy imparted can be provided as a single input of energy or as repeated inputs of smaller portions of energy.

[0027] Examples of suitable forms of mechanical energy input include impact parallel to a wall, energy input via a weight or punch on a mounted menthol particle, preferably in the form of a sudden impact, active accelerated vertical drop or free fall.In a preferred embodiment of the method, the mechanical energy input is provided by free fall onto an inelastic surface.The drop height can be, for example, within the range of 1.0 to 5 m, for example within the range of 1 to 3 m, for example 1.5 m or 2 m.

[0028] In one embodiment of the present invention, the mechanical energy is applied when 20 kg of menthol particles are - packed in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; - the bags are packed in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; - The box is dropped once from a height of at least 1.0 m and up to a height of 5 m, preferably up to a height of 3 m, onto an inelastic surface in a plane parallel to the sides formed by L(box) and H(box). can be given in case.

[0029] Surprisingly, it has been found that by combining storage according to the invention with the input of mechanical energy according to the invention it is possible to obtain advantageous menthol particles stabilized against caking.

[0030] Using the process of the invention it is possible to obtain menthol particles which are stabilized against caking and whose shape, size or number of particles generally corresponds to those of the menthol particles used.

[0031] In one embodiment of the method, the method is carried out such that the number of particles at the end of the method is still at least 50%, in particular at least 60%, preferably at least 70%, preferably at least 80% of the number of particles used at the start of the method.

[0032] In one embodiment of the process, said process is carried out in such a way that at least 50% by weight, in particular at least 60% by weight, preferably at least 70% by weight, preferably at least 80% by weight, of the menthol particles stabilized against caking according to the invention have the same shape as the menthol particles used.

[0033] In one embodiment of the process, said process is carried out in such a way that at least 50% by weight, in particular at least 60% by weight, preferably at least 70% by weight, preferably at least 80% by weight, of the menthol particles stabilized against caking according to the invention are of the same size as the menthol particles used.

[0034] Those skilled in the art can implement these embodiments, for example, by limiting the input of mechanical energy or through the nature of the input of mechanical energy selected.

[0035] In one embodiment of the method, the method is carried out such that the menthol particles are only provided with enough energy so that at least 50% by weight, preferably at least 60% by weight, in particular at least 70% by weight, preferably at least 80% by weight, of the particles retain their size.

[0036] In one embodiment of the method, the method is carried out such that the menthol particles are only provided with enough energy so that at least 50% by weight, preferably at least 60% by weight, in particular at least 70% by weight, preferably at least 80% by weight, of the particles retain their shape.

[0037] Menthol particles are understood for the purposes of the present invention as meaning individual particles of menthol in solid form.

[0038] "Menthol particles", "menthol particles used" and "used menthol particles" refer to particles that are used as starting product for the process of the present invention. The term "menthol particles stabilized against caking" refers to particles that are obtained by the process of the present invention.

[0039] The size of a menthol particle refers to the longest dimension in space of the particle of any shape. Thus, for a menthol particle that is spherical, the size of the particle is the diameter of the sphere, and for a menthol particle that is rectangular, the size of the particle is the diagonal of the rectangular prism.

[0040] In one preferred embodiment of the invention, menthol particles are used having a size in the range of 1 to 35 mm, in particular 4 to 35 mm, in particular 5 to 30 mm, preferably 10 to 25 mm, preferably 12 to 24 mm, in particular 15 to 20 mm.

[0041] In a preferred embodiment of the present invention, menthol particles are used having a size in the range of 4-35 mm, in particular in the range of 5-30 mm, preferably in the range of 10-25 mm, preferably in the range of 12-24 mm, in particular in the range of 15-20 mm, of which the content of menthol particles below 4 mm in size is less than 5% by weight, preferably less than 2% by weight and in particular less than 1% by weight, very preferably less than 0.5% by weight and particularly preferably less than 0.1% by weight.

[0042] The size and particle size distribution of the particles can be determined, for example, by microscopy or by sieve analysis.

[0043] A shaped body refers to the geometric shape of a three-dimensional figure represented by its surface. The surface of a shaped body may consist of flat or crowned surfaces. The term shape is hereinafter used synonymously with the term shaped body.

[0044] Menthol particles are also known as a wide variety of shaped bodies, such as needles, polyhedrons, cubes, cuboids, cones, prisms, spheres, hemispheres, spherical disks, cylinders, beads and mixed forms thereof, etc. Shaped bodies are provided herein by the nature of the production.

[0045] Needle crystals are obtained, for example, by crystallizing L-menthol from a solution or melt containing L-menthol. Needle crystals typically have a length of 0.5-3 cm and a thickness of 1-3 mm. Needle crystals are characterized as being shaped bodies that, as a result of their manufacturing process, have a geometric shape in which only one dimension in space is a multiple of the other dimension in space. Compacts (synonyms: compacted crystals / tablets) are obtained by compression of crystals and, depending on the compression type, can be in the form of, for example, spheres, cubes, cuboids, pincushions or chains. Pellets can be obtained, for example, by dropping a menthol melt onto a cooled surface. Spherical particles can be obtained, for example, by dropping a menthol melt into water. Flakes can be obtained, for example, by contacting a menthol melt with two spaced apart cooled surfaces.

[0046] The method of the present invention is suitable for menthol particles of any shape. Preferred menthol particles for the purposes of the present invention are menthol particles in the form of flakes, spheres or pellets. Menthol particles in the form of flakes are particularly preferred.

[0047] A flake is, for the purposes of the present invention, a shaped body in which at least two surfaces of the shaped body are parallel to each other. For the purposes of the present invention, a flake is understood to mean in particular a shaped body in which the two largest surfaces of the shaped body are parallel to each other.

[0048] The distance between two parallel surfaces is referred to as the flake thickness. If more than two surfaces are parallel to each other, the smallest distance between two such surfaces is referred to as the flake thickness.

[0049] Flakes are understood in particular to mean bodies having at least two surfaces parallel to one another and whose other dimension in space (referred to as the average side length of the flake) is at least 1.25 times its thickness.

[0050] Flakes are understood to mean in particular bodies having at least two surfaces parallel to one another, with the exception of bodies in which only one dimension in the space of the body is a multiple (at least three times) of the thickness.

[0051] Examples of flakes are thus rectangular prisms or cubes. Flakes are also produced by crushing, in particular by breaking, a film, and are bodies in which the surfaces not formed by parallel surfaces are not formed at right angles to the surfaces formed by the parallel surfaces.

[0052] A sphere, for the purposes of the present invention, is a shaped body in which all surfaces of the shaped body are convex. Examples of spheres thus include balls, pincushions or beads.

[0053] A pellet, for purposes of the present invention, is a shape characterized by having a flat surface and a crowned surface opposite the flat surface.

[0054] Examples of menthol particles suitable as starting products for the process of the present invention are flakes as described in WO 2008 / 152009 (BASF) or US 3,023,253 and US 3,064,311, pellets as described in WO 2016 / 034481 (Sandvik), pellets as described in WO 2016 / 016154 (Symrise) or compacts as described in WO 03 / 101924 (Symrise).

[0055] Particularly preferred are menthol particles in which the menthol is present in the form of L-menthol. Particularly preferred are menthol particles in which the menthol content, in particular the L-menthol content, is greater than 80% by weight, in particular greater than 90% by weight, in particular greater than 99.5% by weight, preferably greater than 99.7% by weight, based on the total weight of the particle.

[0056] The melt of L-menthol of formula (I) is suitable as starting material for producing the menthol particles used according to the invention.

[0057] [ka] IUPAC name: 1R,2S,5R-2-isopropyl-5-methylcyclohexanol Here, the melted menthol may be of natural or synthetic origin and usually has an enantiomeric excess of at least 95%, 96% or 97% ee to 100% ee, preferably 98%, 98.5% or 99% to 99.9% ee. Particularly suitable starting materials in the context of the method of the invention are melts of L-menthol with a content of L-menthol of at least 95%, 96% or 97% by weight or more, preferably at least 98% to 100% by weight, and very preferably 98%, 98.5% or 99% to 99.9% by weight (in each case relative to the total weight of the melt) with impurities, such as residual solvents, diastereomers of L-menthol of formula (I) or by-products originating from the synthesis or isolation method.

[0058] It is preferable to use an L-menthol melt containing 0.1% to 50% by weight, in particular 1% to 40% by weight, in particular 5% to 35% by weight, preferably 10% to 30% by weight, of menthol seed crystals.

[0059] The weight percentage of the seed crystals is in each case based on the total weight of the mixture of melt and seed crystals used.

[0060] It is preferable to use an L-menthol melt which comprises 0.1% to 50% by weight, in particular 1% to 40% by weight, in particular 5% to 35% by weight, preferably 10% to 30% by weight, of menthol seed crystals, the remaining part by weight being constituted by an amount of L-menthol in molten form.

[0061] An L-menthol melt is therefore understood as meaning, for example, L-menthol comprising from 50% to 99.9% by weight, 60% to 99% by weight, in particular 65% to 95% by weight, preferably 70% to 90% by weight of menthol in molten form.

[0062] The L-menthol melt that is preferably used is therefore a suspension of seed crystals and molten L-menthol.

[0063] The crystals of L-menthol, called seed crystals, can be obtained in a conventional manner, for example by crystallizing L-menthol from a solution or melt containing L-menthol and adding it to the L-menthol melt. This can be done, for example, by stirring in a storage container or by scattering pre-crushed L-menthol crystals on the L-menthol melt (liquid crystal film) used. It is also possible to produce seed crystals using a scraped surface cooler or extruder as described below and add them to the L-menthol melt. It is further possible to use fine grain fractions as described below as seed crystals.

[0064] It is also possible to produce seed crystals in the L-menthol melt before contacting it with the cooling surface. Examples of suitable methods for producing seed crystals in the L-menthol melt are the use of a scraped surface cooler or the use of an extruder.

[0065] One embodiment of the present invention features seed crystals formed by processing the used menthol melt in a scraped surface cooler.

[0066] In a preferred embodiment, seeding is achieved by passing the melt through a heat exchanger operated below the melting point, the walls of which are free of crystallized material due to abrasive elements, which consist of at least one planar element, preferably a plurality of them. An example of a planar element is a scraper. Such a configuration is known as a scraped surface cooler and is described, for example, in G. Arkenbout, Melt Crystallization Technology, Technomic Publishing Co., 1995, p. 230. A suitable scraped surface cooler has a cylindrical cooling inner surface, which is swept by a scraper arranged, for example, on a rotating shaft.

[0067] In one embodiment, seed crystals of L-menthol are used, obtained by processing the L-menthol melt used in a scraped surface cooler, the seed crystals being formed in situ in the solidifying L-menthol melt, thereby avoiding further work steps.

[0068] In one embodiment, the temperature in the scraped surface cooler is set in the range of 10-32° C., in particular 15-20° C. The temperature can be set using a cooling liquid, in particular water. The menthol melt can be conveyed in a single pass through the scraped surface cooler. It is likewise possible to circulate the menthol melt through the scraped surface cooler multiple times until the desired proportion of seed crystals is produced.

[0069] One embodiment features seed crystals formed by processing the menthol melt used in the extruder.

[0070] A heat exchanger having an abrasive element, including at least one helical element, is referred to for the purposes of the present invention as an extruder. Such a configuration is described, for example, in CM Van't Land, Industrial Crystallization of Melts, Marcel Dekker, 2005, pp. 161-167.

[0071] The grinding element may comprise one or more devices with helical elements, for example one screw or in particular two screws (so-called twin screws). The devices may be of co-rotating or counter-rotating configuration. The devices may be of interlocking or non-interlocking configuration. In addition to the helical elements that generally mainly serve for conveying, each device of the grinding element may comprise further elements that usually serve for mixing. An example of such an element is a kneading block. The grinding element device usually has different zones of helical elements and mixing elements.

[0072] In one embodiment, a heat exchanger with counter-rotating twin screws is used as the extruder.

[0073] In one embodiment, a heat exchanger with co-rotating twin screws is used as the extruder. It is preferred to use a heat exchanger with co-rotating twin screws as the extruder, the screws being in an interlocking configuration.

[0074] In one embodiment, the temperature of the extruder is set below 42°C, preferably at a temperature between 5 and 40°C, in particular in the range between 10 and 32°C, in particular between 15 and 20°C. In a further embodiment, the temperature at the inlet and / or outlet of the extruder can be set higher than in the area between them. The temperature can be set using a cooling liquid, in particular water. The menthol melt can be conveyed in a single pass through the extruder. It is likewise possible to circulate the menthol melt through the extruder multiple times until the desired proportion of seed crystals is produced.

[0075] In one embodiment, seed crystals of L-menthol obtained by processing the L-menthol melt used according to the invention in an extruder are used, the seed crystals being formed in situ in the solidifying L-menthol melt, thereby avoiding further work steps.

[0076] The proportion of seed crystals in the menthol melt can be determined, for example, by measuring the density, the viscosity of the L-menthol melt, the power usage of a scraped surface cooler, or optically, for example with a scattered light probe.

[0077] In a preferred embodiment, the proportion of seed crystals in the L-menthol melt is determined by measuring the density. The density of L-menthol crystals in the alpha modification is 900 kg / m at 15° C. 3 The densities of menthol melts at various temperatures are described, for example, in Ishchenki, ED, Roshchina, GP Ukr Fiz Zh Ukr., eds., 1963, Vol. 8, No. 11, pp. 1241-1249.

[0078] The proportion of seed crystals is usually measured at the exit of scraped surface cooler or extruder.If the desired proportion of seed crystals is not achieved, the menthol melt can be returned to scraped surface cooler or extruder until the desired proportion of seed crystals is achieved in the menthol melt, no matter how long it takes.Alternatively, seed crystals can be added to the L-menthol melt.

[0079] The L-menthol melt used to produce the menthol particles is usually used at a temperature in the range of about 40-60° C., preferably about 43-50° C. At temperatures in the range below 42-43° C., i.e. below the melting point of L-menthol, the L-menthol melt is a supercooled melt.

[0080] In a preferred embodiment of the process of the invention, menthol particles in the form of flakes are used. These can be obtained, for example, by applying a melt of L-menthol to a cooled surface, for example a submerged roller. The film of menthol crystallized on the submerged roller can be subjected to a post-treatment consisting of a heat treatment by the introduction of heat and a strengthening by the application of additional menthol. Menthol particles in the form of flakes can also be obtained, for example, by applying a menthol melt between a pair of counter-rotating cooling rollers.

[0081] In a preferred embodiment of the process, menthol particles in the form of flakes having a thickness of 0.2 to 15 mm, preferably 4 to 10 mm, in particular 6 to 8 mm, are used.

[0082] In a preferred embodiment of the process, menthol particles in the form of flakes having an average side length of 5 to 25 mm, preferably 12 to 16 mm, are used.

[0083] In a preferred embodiment of the process, menthol particles are used in the form of flakes having a thickness of 0.2 to 15 mm, preferably 4 to 10 mm, in particular 6 to 8 mm, and an average side length of 5 to 25 mm, preferably 12 to 16 mm.

[0084] In a preferred embodiment of the method, menthol particles in the form of flakes are used having a size in the range of 1 to 35 mm, in particular 4 to 35 mm, in particular 5 to 30 mm, preferably 10 to 25 mm, preferably 12 to 24 mm, in particular 15 to 20 mm.

[0085] In a preferred embodiment of the method, menthol particles in the form of flakes are used having a size in the range of 4-35 mm, in particular in the range of 5-30 mm, preferably in the range of 10-25 mm, preferably in the range of 12-24 mm, in particular in the range of 15-20 mm, of which the content of menthol particles below 4 mm in size is less than 5% by weight, preferably less than 2% by weight and in particular less than 1% by weight, very preferably less than 0.5% by weight and particularly preferably less than 0.1% by weight.

[0086] A preferred embodiment of the method uses menthol particles in the form of flakes obtained by contacting the menthol melt with two spaced apart cooled surfaces, which involves solidification of the menthol melt into menthol, while maintaining contact between the solidifying menthol melt and the cooled surfaces at least until solidification is complete.

[0087] It is advantageous to use a menthol melt as described above. It is preferable to use an L-menthol melt which contains 0.1% to 50% by weight, in particular 1% to 40% by weight, in particular 5% to 35% by weight, preferably 10% to 30% by weight of menthol seed crystals.

[0088] The L-menthol melt can be transported between two spaced apart cooling surfaces, for example, via a weir or via a thermostatically controlled transport pipeline.

[0089] In this embodiment, the L-menthol melt used is contacted with two spaced apart cooled surfaces. The L-menthol melt used is preferably present in the space between the two spaced apart cooled surfaces. The contact of the melt with the respective surfaces can be carried out simultaneously, i.e. at the same time, or at staggered intervals.

[0090] The processing requirements usually mean that the contact of the used L-menthol melt with the two cooled surfaces is carried out at staggered intervals, for example by first applying the melt to an area of ​​one of the two surfaces that is not actively cooled, which is then cooled for a short time and then contacted with the second cooled surface.

[0091] The processing requirements usually mean that the contact of the used L-menthol melt with the two cooling surfaces is carried out at staggered intervals, so that the melt first comes into contact with one of the cooling surfaces and then immediately thereafter with the second cooling surface. Depending on the temperature difference between the used L-menthol melt and the cooling surface with which it is first contacted, it has proven advantageous here to keep the time interval between the contact of the L-menthol melt with each of the cooling surfaces as short as possible, so that total or complete solidification of the used L-menthol melt does not occur before the contact with the second cooling surface is established. The time interval between the contact of the used L-menthol melt with the respective surface is usually not more than 30 seconds, preferably a maximum of 20 seconds, and more preferably a maximum of 10 seconds.

[0092] In one embodiment, the cooling surfaces used are in each case smooth surfaces, preferably flat sections of continuous belts made of steel, other metals, plastics or combinations of said materials. Particularly preferred are continuous belts made of smooth or polished stainless steel.

[0093] The duration of the contact of the used melt or the solidified melt with the two cooling surfaces is referred to below as the contact time and can be the same or different for each surface. As mentioned above, the contact is often performed at staggered intervals and the end of the contact time is usually staggered, i.e. the end of the contact of the fully solidified L-menthol melt with each cooling surface is performed at different times, so that the contact time of the melt with each cooling surface is usually of different duration. Whatever the order in which the contact of the melt with each of the two cooling surfaces and the stripping of the fully solidified L-menthol melt from the surfaces are performed, the contact times of the individual cooling surfaces overlap so that the used L-menthol melt / solidified L-menthol melt is in contact with both cooling surfaces simultaneously for a selectable time.

[0094] In this embodiment, the contact between the solidifying L-menthol melt and the cooling surface is maintained at least until the solidification is complete. The solidification / crystallization of the used L-menthol melt is preferably not considered complete until at least about 80% by weight or better 85% to 100% by weight, preferably 90% to 100% by weight, preferably 95% by weight or 97% to 99.5% by weight, and very particularly preferably 98% to 99% by weight of the L-menthol in the obtained solid form is present in the alpha modification. The specific modification of the obtained solidified L-menthol can be determined using methods known to the skilled person, for example X-ray diffraction or powder diffraction methods (see for example Joel Bernstein, Polymorphism in Molecular Crystals, Oxford University Press, 2002, pages 94 to 150).

[0095] The term "cooling surface" is understood to mean a surface having a temperature below the melting / freezing point of L-menthol, which is 42-43° C., or thermostatically controlled at such a temperature. The cooling surfaces used, each independently of the other, usually have a temperature in the range of about 0 to about 40° C., preferably about 0 to about 35° C., particularly preferably 5-30° C., and very particularly preferably in the range of 10-25° C., in particular 15-20° C. The two surfaces here can both have the same or different temperatures. It is also possible to change the temperature of the cooling surfaces individually during the course of the respective contact times, i.e. to increase or decrease the temperature.

[0096] In a preferred embodiment the two cooling surfaces have a planar parallel orientation and are typically separated by a distance of 0.2 to 15 mm, preferably 2 to 10 mm, in particular 3 to 9 mm, in particular 5 to 8 mm, in particular 6 to 8 mm.

[0097] The term "planar parallel orientation" is understood to mean that the two cooling surfaces are separated by the same distance over the entire area or partial area of ​​contact with the solidifying L-menthol melt, within the limits of normal measurement accuracy. It is advantageous if the intervening space formed between the two cooling surfaces is completely filled with L-menthol, since this ensures the largest possible contact area between the cooling surfaces and the solidifying L-menthol melt.

[0098] Depending on the proportion of seed crystals in the L-menthol melt used, the selected temperature of the L-menthol melt used, as well as the separation distance and temperature of the two cooling surfaces, the contact time of the solidifying L-menthol melt with the two cooling surfaces is selected so that solidification is complete. Usual contact times are in the range of 10 to 300 seconds, preferably 120 to 240 seconds. Solidification is usually complete after a contact time of about 10 to about 300 seconds, preferably about 20 to about 250 seconds, preferably up to about 200 seconds and very particularly preferably 30 to 150 seconds, preferably up to 100 seconds. The specified contact times are understood here as describing a time interval during which there is simultaneous contact between the L-menthol melt / solidifying or already solidified L-menthol melt with both cooling surfaces. It is also possible to extend beyond this time for the contact of the solidified L-menthol melt with one of the two cooling surfaces.

[0099] In a preferred embodiment, short contact times and complete solidification can be achieved by adding seed crystals to the melt before or during contact with the cooling surface.

[0100] In a particularly preferred embodiment, the method is carried out using a double belt cooler, which is known to those skilled in the art and can be obtained, for example, from Ipco Germany GmbH, 70736 Fellbach, Germany or SBS Steel Belt Systems SrL, Italy.

[0101] When using the mentioned double belt cooler, it is understood that the cooling surface used is realized in the form of two continuous belts (cooling belts), usually made of steel and moved in counter-rotation on rollers (see CM van't Land, Industrial Crystallization of Melts, Marcel Dekker, 2005, p. 63). The solidification of the L-menthol melt into solid form L-menthol then takes place in the space between the plane-parallel parts of the two cooling belts of the double belt cooler facing each other.

[0102] In order that the contact of the solidifying L-menthol melt with the two cooling belts is achieved as simultaneously as possible, it is expedient to bring the melt into contact with the cooling belts as close as possible to the point where the space between the planar parallel parts of the two cooling belts begins, so that incomplete solidification of the L-menthol melt is kept to a minimum.

[0103] The preferred method for producing menthol particles in the form of flakes can be carried out batchwise, for example using a cooling punch, or continuously, for example using a double belt cooler as described above. Continuous methods have economic advantages, particularly here.

[0104] The solidified L-menthol film obtained can then be removed from the cooling surface by methods known to those skilled in the art. Depending on how the method is carried out, the L-menthol film can either fall directly from the cooling surface or be peeled off from one or both of the cooling surfaces using a knife attachment. When the solidified L-menthol film is peeled off from one or both of the cooling surfaces, preferably from the cooling belt of the double belt cooler preferably used, L-menthol particles in the form of flakes are obtained.

[0105] These can be adjusted to the desired size of L-menthol flakes using suitable post-processing methods. Examples of post-processing methods include crushing, for example using pin crushers, cam crushers, single-shaft crushers, circular blade shears, impact crushers, or using jaw crushers, and also crushing by sieving. The crushing is preferably carried out using grinders operated at low speeds, for example in the range of 0.2 m / s to 10 m / s, especially in the range of 0.5 m / s to 2.0 m / s.

[0106] Additionally, particles of a certain size can be removed by sieving. The post-treatment methods mentioned may be used in any combination with each other.

[0107] The so obtained menthol particles in flake form can be further processed by further cooling, for example on a cooling screw conveyor or a cooling conveyor belt (before or after any post-processing is carried out).

[0108] Through the preferred method for producing menthol particles in the form of flakes, it is possible to obtain L-menthol particles in the form of flakes having at least two smooth surfaces as a result of solidification in contact with two cooling surfaces.

[0109] Depending on the selected distance between the two cooling surfaces, the menthol particles obtained by the preferred method for producing menthol particles in flake form have a thickness of 0.2 to 15 mm, preferably 2 to 10 mm, in particular 3 to 9 mm, in particular 5 to 8 mm, in particular 6 to 8 mm.

[0110] The size of the flakes can be freely selected according to the nature of the post-treatment and can range from continuous strips to substantially crushed flakes.In one embodiment, particles with a size below 4 mm (so-called fine fraction) can be removed, for example, by sieving.In one embodiment, the fine fraction thus separated can then be added as seed crystals into the solidifying L-menthol melt.

[0111] In a preferred embodiment, menthol particles are obtained in the form of flakes having a size in the range of 1 to 35 mm, in particular 4 to 35 mm, in particular 5 to 30 mm, preferably 10 to 25 mm, preferably 12 to 24 mm, in particular 15 to 20 mm.

[0112] In a preferred embodiment, menthol particles are obtained in the form of flakes having a size in the range of 4-35 mm, in particular 5-30 mm, preferably 10-25 mm, preferably 12-24 mm, in particular 15-20 mm, of which the content of menthol particles below 4 mm in size is less than 5% by weight, preferably less than 2% by weight and in particular less than 1% by weight, very preferably less than 0.5% by weight and particularly preferably less than 0.1% by weight.

[0113] The L-menthol particles in flake form thus obtained are particularly suitable as menthol particles used for producing menthol particles stabilized against caking.

[0114] The present invention further provides the use of the menthol particles stabilized against caking obtained by the process of the present invention in or in the manufacture of daily necessities and consumer goods, such as pharmaceutical or cosmetic products, foodstuffs, hygiene or cleaning articles, confectionery or tobacco products.

[0115] The present invention further provides menthol particles stabilized against caking obtainable by the process of the present invention.

[0116] A common problem with the storage of menthol particles is their limited shelf life. Particularly menthol particles in the form of flakes, spheres and pellets exhibit the so-called caking phenomenon after storage. This imposes obvious limitations on the use of the stored particles.

[0117] One object of the present invention was therefore to provide menthol particles with increased storage stability.

[0118] Surprisingly, 20 kg of menthol particles can be molded into a) packaged in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; The bags are packaged in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a corrugated board thickness of 6 mm; b) the box is stored at 20° C. for 10 days on the side formed by L(box) and H(box), c) This is then dropped once from a height of 1.5 m onto an inelastic surface, in a plane parallel to the sides formed by L(box) and H(box). It has been found that the resulting menthol particles have increased storage stability.

[0119] The present invention relates to a method for manufacturing a menthol granule having a weight of 20 kg, which is molded and then a) packaged in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; The bags are packaged in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a corrugated board thickness of 6 mm; b) the box is stored at 20° C. for 10 days on the side formed by L(box) and H(box), c) This is then dropped once from a height of 1.5 m onto an inelastic surface, in a plane parallel to the sides formed by L(box) and H(box). In some cases, Storage stability S=[(Z1-Z2) / Z1] is 0.25 or less, particularly 0.2 or less, preferably 0.1 or less, where Z1 is the number of particles after molding and Z2 is the number of particles 20 weeks after molding; Further provided are storage-stable menthol particles.

[0120] As a measure of the storage stability S, the number of particles is determined immediately after molding and after 20 weeks.

[0121] Storage stability is defined for the purposes of this invention as S=[(Z1-Z2) / Z1], where Z1 is the number of particles after molding and Z2 is the number of particles 20 weeks after molding.

[0122] For the determination of the number of particles Z1, a defined mass of particles (e.g. 100 g) is weighed out and counted after molding. For the determination of the number of particles Z2, an equal amount of particles (e.g. 100 g) is weighed out and counted 20 weeks after molding. The number of particles can be determined, for example, by microscopy.

[0123] During the 20 weeks between molding and particle determination, the particles are typically kept at a temperature of 0 to 30°C, particularly 20 to 25°C, particularly 20°C.

[0124] In one preferred embodiment of the invention, the storage stability S is equal to or less than 0.2, in particular equal to or less than 0.1, in particular equal to or less than 0.05, preferably equal to or less than 0.01, in particular equal to or less than 0.001.

[0125] Increased particle numbers, for example as a result of implementing stability measures, are also encompassed by the present invention.

[0126] In a further embodiment of the invention, the storage stability is within the range of -0.25 to 0.25, in particular -0.2 to 0.2, preferably -0.1 to 0.1, in particular -0.05 to 0.05, preferably -0.001 to 0.001.

[0127] The number of particles 20 weeks after molding is preferably the same as the number of particles after molding, in which case the storage stability S=0.

[0128] In one embodiment of the present invention, the storage stability S is in the range of 0 to 0.25, particularly in the range of 0 to 0.2, particularly 0 to 0.1, particularly 0 to 0.05, particularly 0 to 0.01, and particularly 0 to 0.001.

[0129] All the above-mentioned menthol particles are suitable as storage-stable menthol particles.

[0130] A preferred embodiment of the present invention provides storage stable menthol particles having a size within the range of 1 to 35 mm, particularly 4 to 35 mm, in particular 5 to 30 mm, preferably 10 to 25 mm, preferably 12 to 24 mm, in particular 15 to 20 mm.

[0131] A preferred embodiment of the present invention provides storage-stable menthol particles having a size in the range of 4-35 mm, in particular in the range of 5-30 mm, preferably 10-25 mm, preferably 12-24 mm, in particular 15-20 mm, of which the content of menthol particles below 4 mm in size is less than 5% by weight, preferably less than 2% by weight and in particular less than 1% by weight, very preferably less than 0.5% by weight and particularly preferably less than 0.1% by weight.

[0132] Particularly preferred are storage-stable menthol particles having a menthol content, in particular an L-menthol content, of more than 80% by weight, in particular more than 90% by weight, in particular more than 99.5% by weight, preferably more than 99.7% by weight, based on the total weight of the particle.

[0133] Storage-stable menthol particles in which menthol is present in the L-menthol form are particularly preferred.

[0134] Particularly preferred are storage-stable menthol particles in the form of flakes, spheres or pellets, preferably in the form of flakes.

[0135] Further preferred are storage-stable menthol particles present in the form of flakes having a thickness of 0.2 to 15 mm, preferably 4 to 10 mm, in particular 6 to 8 mm.

[0136] Particularly preferred are storage-stable menthol particles in the form of flakes obtained by contacting a menthol melt with two spaced apart cooled surfaces, which involves solidification of the menthol melt into menthol, while maintaining contact between the solidifying menthol melt and the cooled surfaces at least until solidification is complete.

[0137] The storage stability of the so obtained storage stable menthol particles makes them particularly suitable for the manufacture or use in daily necessities and consumer goods.

[0138] The present invention therefore further provides the use of the storage-stable menthol particles obtained according to the invention in the manufacture of or in daily necessities and consumer goods, such as pharmaceutical or cosmetic products, foodstuffs, hygiene or cleaning articles, confectionery or tobacco products.

[0139] A further object of the present invention was to provide a process which makes it possible to obtain a menthol melt with a defined content of seed crystals as high as possible. Such a process should advantageously allow long operating times.

[0140] Surprisingly, it has been found that extruders are suitable for producing menthol crystals. Such crystals obtained in this way can be used directly or can be converted into various shaped bodies by compression. The crystals can also be added to a menthol melt, for example as seed crystals, and this menthol melt with seed crystals can then be used in the production of menthol particles in a wide variety of forms, for example in the form of flakes or pellets. Surprisingly, it has also been found that using the method of the present invention, it is possible to adjust the menthol melt to a desired content of menthol crystals and to use the suspension of menthol crystals and molten menthol thus obtained for the production of menthol particles in a wide variety of forms, for example in the form of flakes or pellets. Compared with the known prior art methods of producing menthol melts with a defined content of seed crystals, the method of the present invention has the distinctive feature of an increased working time.

[0141] The present invention therefore further provides a method for producing crystals of menthol, in particular L-menthol, wherein the menthol melt is conveyed through an extruder.

[0142] The present invention therefore further provides a method for producing a menthol melt, in particular an L-menthol melt, comprising 0.1% by weight to 50% by weight of menthol, in particular L-menthol seed crystals, wherein the menthol melt is conveyed through an extruder.

[0143] A heat exchanger having an abrasive element, including at least one helical element, is referred to for the purposes of the present invention as an extruder. Such a configuration is described, for example, in CM Van't Land, Industrial Crystallization of Melts, Marcel Dekker, 2005, pp. 161-167.

[0144] The grinding element may comprise one or more devices with helical elements, for example one screw or in particular two screws (so-called twin screws). The devices may be of co-rotating or counter-rotating configuration. The devices may be of interlocking or non-interlocking configuration. In addition to the helical elements that generally mainly serve for conveying, each device of the grinding element can usually comprise further elements that mainly serve for mixing. An example of such an element is a kneading block. The grinding element device usually has different zones of helical elements and mixing elements.

[0145] In one embodiment, a heat exchanger with counter-rotating twin screws is used as the extruder. In one embodiment, a heat exchanger with co-rotating twin screws is used as the extruder. It is preferred to use a heat exchanger with co-rotating twin screws as the extruder, the screws being in a geared configuration.

[0146] The menthol melt can be conveyed through the extruder by the rotation of the abrasive elements or can be conveyed through the extruder with the further assistance of, for example, a pump.

[0147] In one embodiment of the invention, the temperature of the extruder is set below 42°C, preferably at a temperature between 5 and 40°C, in particular in the range between 10 and 32°C, in particular between 15 and 20°C. In a further embodiment, the temperature at the inlet and / or outlet of the extruder can be set higher than in the area between them. The temperature can be set using a cooling liquid, in particular water. The menthol melt can be conveyed in a single pass through the extruder. It is likewise possible to circulate the menthol melt through the extruder multiple times until the desired proportion of seed crystals is produced.

[0148] The present invention therefore further provides the following embodiments: 1. A process for producing crystals of menthol, in particular L-menthol, in which a menthol melt is conveyed through an extruder. 2. A process for producing a menthol melt, in particular an L-menthol melt, containing 0.1% to 50% by weight of menthol seed crystals, wherein the menthol melt is conveyed through an extruder. 3. The method of any of the preceding embodiments, wherein the polishing element of the extruder comprises a device having a helical element. 4. The method of any of the preceding embodiments, wherein the polishing element of the extruder comprises more than one device with a helical element, preferably two or three devices. 5. The method of embodiment 4, wherein the abrasive element of the extruder is a twin screw. 6. The method of any of the previous embodiments, wherein the apparatus comprises at least one helical element and at least one mixing element. 7. The method of any of the preceding embodiments 4-6, wherein the apparatus is in a co-rotating configuration. 8. The method of any of the preceding embodiments 4-6, wherein the device is in a counter-rotating configuration. 9. The method of any one of the preceding embodiments 4 to 8, wherein the devices are in a linked configuration. 10. The method of any one of the preceding embodiments 4 to 8, wherein the devices are in a non-interlocking configuration. 11. The method of any of the preceding embodiments, wherein the menthol melt is conveyed through a heat exchanger through the rotation of the abrasive elements. 12. The method of any of the preceding embodiments, wherein the menthol melt is conveyed through the heat exchanger using a pump. 13. The method according to any of the preceding embodiments, wherein the extruder temperature is set below 42°C, in particular in the range of 5 to 40°C, preferably 10 to 32°C. 14. A method for producing menthol particles, comprising: a. producing a menthol melt containing menthol seed crystals by conveying the menthol melt through an extruder; b. contacting the menthol melt so obtained with at least one cooled surface. 15. The method according to embodiment 14, wherein a menthol melt obtained according to any one of embodiments 2 to 13 is used. 16. The method according to embodiment 14 or 15, wherein the obtained menthol melt is contacted with two spaced apart cooling surfaces, preferably in the form of a double belt cooler. EXAMPLES

[0149] Grading system for assessing caking: 0 = completely free flowing, no caking 1 = slight caking, easily loosened by hand 2 = Heavy caking, may be difficult to separate or may not separate at all

[0150] I. Examples of the Invention [Examples 1A-3, 1B-1 and 1D-2] The menthol particles used were menthol flakes produced according to examples A-3, B-1 and D-2. Immediately after moulding, 20 kg of menthol particles were transferred into bags made of a polyethylene film with a thickness of 0.12 mm, with dimensions of 660 mm [= L (bag)] x 690 mm [= W (bag)], the bags were sealed and the bags were packed into a box. The box used was made of double-walled corrugated board and had internal dimensions of 385 mm length [= L (box)], 320 mm width [= W (box)], 450 mm height [= H (box)] and a cardboard thickness of 6 mm. The compression resistance (DIN 55440) F of the container of the box is 4500 N, the weight is 0.8 kg and the prefabricated edge is 40 mm. It is a prefabricated box according to FEFCO 0201. The boxes were closed with adhesive tape and stored at 20°C for 7 days on the area formed by L(box) and H(box). The boxes were then dropped from a height of 1.5 m onto the ground (concrete floor). This was done by lifting the boxes to a height of 1.5 m using the transport arm of a drop robot and then allowing them to freely fall onto the concrete floor. The area of ​​impact of the boxes is the area of ​​the boxes formed by L(box) and H(box).

[0151] The boxes so treated were opened immediately after the input of mechanical energy and 18 weeks after the input of mechanical energy (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three examples 1A-3, 1B-1 and 1D-2, the degree of caking of the menthol particles was rated as “0” both immediately after the input of mechanical energy and after 18 weeks.

[0152] [Examples 2A-3, 2B-1 and 2D-2] Examples 1A-3, 1B-1 and 1D-2 were repeated with storage for 14 days before input of mechanical energy.

[0153] The boxes so treated were opened immediately after the input of mechanical energy and after 17 and 18 weeks (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three examples 2A-3, 2B-1 and 2D-2, the degree of caking of the menthol particles was rated as “0” both immediately after the input of mechanical energy and after 17 and 18 weeks.

[0154] [Examples 3A-3, 3B-1 and 3D-2] Examples 1A-3, 1B-1 and 1D-2 were repeated with storage for 21 days before input of mechanical energy.

[0155] The boxes so treated were opened immediately after the input of mechanical energy and after 16, 17 and 18 weeks (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three examples 3A-3, 3B-1 and 3D-2, the degree of caking of the menthol particles was rated as “0” both immediately after the input of mechanical energy and after 16, 17 and 18 weeks.

[0156] [Examples 4A-3, 4B-1 and 4D-2] Examples 2A-3, 2B-1 and 2D-2 were repeated with the box being dropped from a height of 1.0 m.

[0157] The boxes so treated were opened immediately after the input of mechanical energy and 18 weeks after the input of mechanical energy (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three examples 4A-3, 4B-1 and 4D-2, the degree of caking of the menthol particles was rated as “0” both immediately after the input of mechanical energy and after 18 weeks.

[0158] [Examples 5A-3, 5B-1 and 5D-2] Examples 2A-3, 2B-1 and 2D-2 were repeated with the box being dropped from a height of 2.0 m.

[0159] The boxes so treated were opened immediately after the input of mechanical energy and 18 weeks after the input of mechanical energy (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three examples 5A-3, 5B-1 and 5D-2, the degree of caking of the menthol particles was rated as “0” both immediately after the input of mechanical energy and after 18 weeks.

[0160] [Examples 6A-3, 6B-1 and 6D-2] Examples 2A-3, 2B-1 and 2D-2 were repeated, in each case transferring 10 kg of menthol particles into a bag immediately after molding.

[0161] The boxes so treated were opened immediately after the input of mechanical energy and 18 weeks after the input of mechanical energy (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three examples 6A-3, 6B-1 and 6D-2, the degree of caking of the menthol particles was rated as “0” both immediately after the input of mechanical energy and after 18 weeks.

[0162] II. Comparative Example [Examples C1A-3, C1B-1 and C1D-2] Menthol particles without energy input The menthol particles used were menthol flakes produced according to examples A-3, B-1 and D-2. Immediately after moulding, 20 kg of menthol particles were transferred into bags made of a polyethylene film with a thickness of 0.12 mm, with dimensions of 660 mm [= L (bag)] x 690 mm [= W (bag)], the bags were sealed and the bags were packed into a box. The box used was made of double-walled corrugated board and had internal dimensions of 385 mm length [= L (box)], 320 mm width [= W (box)], 450 mm height [= H (box)] and a cardboard thickness of 6 mm. The compression resistance (DIN 55440) F of the container of the box is 4500 N, the weight is 0.8 kg and the assembly edge is 40 mm. It is a prefabricated box according to FEFCO 0201. The box was closed with adhesive tape and stored at 20° C. on the area formed by L(box) and H(box).

[0163] The boxes were opened 18 and 19 weeks after filling and the degree of caking was evaluated based on the rating scale (see above). For all three comparative examples C1A-3, C1B-1 and C1D-2, the degree of caking of the menthol particles was rated as "2" after both 18 and 19 weeks.

[0164] [Examples C2A-3, C2B-1 and C2D-2] Menthol particles with energy input immediately after molding The menthol particles used were menthol flakes produced according to examples A-3, B-1 and D-2. Immediately after moulding, 20 kg of menthol particles were transferred into bags made of a polyethylene film with a thickness of 0.12 mm, with dimensions of 660 mm [= L (bag)] x 690 mm [= W (bag)], the bags were sealed and the bags were packed into a box. The box used was made of double-walled corrugated board and had internal dimensions of 385 mm length [= L (box)], 320 mm width [= W (box)], 450 mm height [= H (box)] and a cardboard thickness of 6 mm. The compression resistance (DIN 55440) F of the container of the box is 4500 N, the weight is 0.8 kg and the assembly edge is 40 mm. It is a prefabricated box according to FEFCO 0201. The boxes were closed with adhesive tape and stored for 2 hours at 20°C on the area formed by L(box) and H(box). The boxes were then dropped from a height of 1.5 m onto the ground (concrete floor). This was done by lifting the boxes to a height of 1.5 m using the transport arm of a drop robot and then allowing them to freely fall onto the concrete floor. The area of ​​impact of the boxes is the area of ​​the boxes formed by L(box) and H(box).

[0165] The boxes so treated were opened immediately after the input of mechanical energy and after 18 and 19 weeks (storage at 20° C.) and the degree of caking was evaluated based on the rating scale (see above). For all three comparative examples C2A-3, C2B-1 and C2D-2, the degree of caking of the menthol particles was rated as “0” immediately after the input of mechanical energy and “2” both after 18 and 19 weeks.

[0166] In other words, the input of mechanical energy according to the present invention results in a reduction in caking, but this only persists if storage according to the present invention occurs prior to the input of mechanical energy.

[0167] III. Examples of menthol particles that can be used in the method of the present invention [Example A-1] The L-menthol melt heated to 50°C was introduced into a scraped surface cooler thermostatically controlled at 10°C. The scraped surface cooler was used to produce menthol seed crystals, the content of which was determined by measuring the density and adjusted to 20% by weight. The so obtained suspension of molten menthol and 20% by weight of menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt thermostatically controlled at 15°C on both sides and with a belt gap set at 4 mm. After a running time of 240 seconds, a crystallized film of L-menthol with a thickness of 4 mm was obtained at the end of the belt, which was crushed by a crusher into flakes with a side length of 5-25 mm. Flakes with a shiny appearance and an average thickness of 4 mm were obtained on both sides. The so obtained flakes had a side length in the range of 5-25 mm, the majority of the flakes having a side length in the range of 10-16 mm.

[0168] [Example A-2] The L-menthol melt, heated to 50°C, was introduced into a scraped surface cooler, thermostatically controlled at 10°C. The scraped surface cooler was used to produce menthol seed crystals, the content of which was determined by measuring the density and adjusted to 20% by weight. The so obtained suspension of molten menthol and 20% by weight of menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt, thermostatically controlled on both sides at 15°C and with a belt gap set at 6 mm. After a running time of 240 seconds, a crystallized film of L-menthol with a thickness of 6 mm was obtained at the end of the belt, which was crushed by a crusher into flakes with a side length of 5-25 mm. Flakes with a shiny appearance and an average thickness of 6 mm were obtained on both sides. The so obtained flakes had a side length in the range of 5-25 mm, the majority of the flakes having a side length in the range of 10-16 mm.

[0169] [Example A-3] The L-menthol melt, heated to 50°C, was introduced into a scraped surface cooler, thermostatically controlled at 10°C. The scraped surface cooler was used to produce menthol seed crystals, the content of which was determined by measuring the density and adjusted to 20% by weight. The so obtained suspension of molten menthol and 20% by weight of menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt, thermostatically controlled on both sides at 15°C and with a belt gap set at 8 mm. After a running time of 240 seconds, a crystallized film of L-menthol with a thickness of 8 mm was obtained at the end of the belt, which was crushed by a crusher into flakes with a side length of 5-25 mm. Flakes with a shiny appearance and an average thickness of 8 mm were obtained on both sides. The so obtained flakes had a side length in the range of 5-25 mm, the majority of the flakes having a side length in the range of 10-16 mm.

[0170] [Example B-1] The L-menthol melt, heated to 50° C., was introduced into a scraped surface cooler, thermostatically controlled at 20° C. The scraped surface cooler was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 10% by weight. The so obtained suspension of molten menthol and 10% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt, thermostatically controlled on both sides at 15° C. and with a belt gap set at 6 mm. After a run time of 240-300 seconds, a crystallized film of L-menthol with a thickness of 6 mm was obtained at the end of the belt. Menthol flakes of the desired size were obtained by pre-comminuted using a pin crusher followed by comminution using a sieve grinder (model 250 D rotor granulator, manufacturer Alexanderwerk, using a sieve insert of 12×24 mm). After subsequent separation of fines using a 4 mm sieve, menthol flakes were obtained with the following size distribution:

[0171] [Table 1]

[0172] The proportion of menthol particles below 4 mm in size was <0.1 wt %.

[0173] [Example B-2] The L-menthol melt heated to 50° C. was introduced into a scraped surface cooler thermostatically controlled at 20° C. The scraped surface cooler was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 10% by weight. The so obtained suspension of molten menthol and 10% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt thermostatically controlled on both sides at 15° C. and with a belt gap set at 8 mm. After a run time of 240-300 seconds, a crystallized film of L-menthol with a thickness of 8 mm was obtained at the end of the belt. Pre-combustion with a pin crusher followed by comminution with a sieve grinder (model 250 D rotor granulator, manufacturer Alexanderwerk, using a sieve insert of 12×24 mm) gave menthol flakes with the following size distribution:

[0174] [Table 2]

[0175] The percentage of menthol particles below 4 mm in size was 12% by weight.

[0176] [Example B-3] The L-menthol melt, heated to 50° C., was introduced into a scraped surface cooler, thermostatically controlled at 20° C. The scraped surface cooler was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 10% by weight. The so obtained suspension of molten menthol and 10% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt, thermostatically controlled on both sides at 15° C. and with a belt gap set at 9 mm. After a run time of 240-300 seconds, a crystallized film of L-menthol, 9 mm thick, was obtained at the end of the belt. Menthol flakes of the desired size were obtained by pre-comminuted using a pin crusher followed by comminution using a sieve grinder (model 250 D rotor granulator, manufacturer Alexanderwerk, using a sieve insert of 12×24 mm). After subsequent separation of fines using a 4 mm sieve, menthol flakes were obtained with the following size distribution:

[0177] [Table 3]

[0178] The proportion of menthol particles below 4 mm in size was <0.1 wt %.

[0179] [Example C-1] The L-menthol melt heated to 50°C was fed into an extruder (outlet temperature 42°C with co-rotating twin screws and integral pump for conveying the L-menthol melt) cooled to 15°C, which was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 30% by weight. The thus obtained suspension of molten menthol and 30% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt thermostatically controlled at 15°C on both sides and with a belt gap set at 6 mm. After a run time of 160 seconds, a crystallized film of L-menthol with a thickness of 6 mm was obtained at the end of the belt. Menthol flakes of the desired size were obtained by pre-comminuted using a pin crusher followed by comminution using a sieve grinder (model 250 D rotor granulator, manufacturer Alexanderwerk, using a sieve insert of 12 x 24 mm). After subsequent separation of fines using a 4 mm sieve, menthol flakes were obtained with the following size distribution:

[0180] [Table 4]

[0181] The proportion of menthol particles below 4 mm in size was <0.1 wt %.

[0182] [Example C-2] The L-menthol melt heated to 50°C was fed into an extruder (outlet temperature 42°C with co-rotating twin screws and integral pump for conveying the L-menthol melt) cooled to 15°C, which was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 30% by weight. The thus obtained suspension of molten menthol and 30% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt thermostatically controlled on both sides at 15°C and with the belt gap set at 8 mm. After a run time of 240 seconds, a crystallized film of L-menthol with a thickness of 8 mm was obtained at the end of the belt. Menthol flakes of the desired size were obtained by pre-comminuted using a pin breaker followed by comminution using a sieve grinder (model 250 D rotor granulator, manufacturer Alexanderwerk, using a sieve insert of 12 x 24 mm). After subsequent separation of fines using a 4 mm sieve, menthol flakes were obtained with the following size distribution:

[0183] [Table 5]

[0184] The proportion of menthol particles below 4 mm in size was <0.1 wt %.

[0185] [Example D-1] The L-menthol melt heated to 50°C was fed into an extruder (outlet temperature 42°C with co-rotating twin screws and integral pump for conveying the L-menthol melt) cooled to 20°C, which was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 20% by weight. The thus obtained suspension of molten menthol and 20% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt thermostatically controlled at 15°C on both sides and with a belt gap set at 7 mm. After a run time of 240 seconds, a crystallized film of L-menthol with a thickness of 7 mm was obtained at the end of the belt. Pre-comminuted with a pin breaker followed by comminution with a sieve grinder (model 250 D rotor granulator, manufacturer Alexanderwerk, using a sieve insert of 12 x 24 mm) gave menthol flakes of the desired size. After subsequent separation of fines using a 4 mm sieve, menthol flakes were obtained with the following size distribution:

[0186] [Table 6]

[0187] The proportion of menthol particles below 4 mm in size was <0.1 wt %.

[0188] [Example D-2] The L-menthol melt heated to 50° C. was fed into an extruder (outlet temperature 42° C. with co-rotating twin screws and integral pump for conveying the L-menthol melt) cooled to 20° C., which was used to produce menthol seed crystals. The seed crystal content was determined by measuring the density and adjusted to 20% by weight. The thus obtained suspension of molten menthol and 20% by weight menthol seed crystals was discharged and applied via a thermostatically controlled pipeline to a double-sided cooling belt thermostatically controlled at 15° C. on both sides and with a belt gap set at 9 mm. After a run time of 240 seconds, a crystallized film of L-menthol with a thickness of 9 mm was obtained at the end of the belt. Pre-grinding with a pin crusher followed by grinding with a sieve grinder (Model 250 D rotor granulator, manufacturer Alexanderwerk, using 12×24 mm sieve insert) gave menthol flakes with the following size distribution:

[0189] [Table 7]

[0190] The percentage of menthol particles below 4 mm in size was 13% by weight. The following is one embodiment of the present invention. (1) A method for producing menthol particles stabilized against caking, comprising storing the menthol particles, after molding, at a temperature of 0 to 30° C. for at least 7 days, and then subjecting the menthol particles to a process for preparing menthol particles stabilized against caking, comprising the steps of: 20 kg of said menthol particles, - packed in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; - the bags are packed in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; - The box is dropped once from a height of 1.0 m onto an inelastic surface with the plane parallel to the sides formed by L(box) and H(box). A method of subjecting a specimen to at least as much mechanical energy as it would be subjected to if the specimen were subjected to (2) The method according to (1), wherein the number of particles at the end of the method is still at least 50% of the number of particles used at the start of the method. (3) The method according to (1) or (2), wherein at least 50% by weight of the menthol particles stabilized against caking are of the same shape as the menthol particles used. (4) The method according to any one of (1) to (3), wherein at least 50% by weight of the menthol particles stabilized against caking are the same size as the menthol particles used. (5) The method according to any one of (1) to (4), wherein the menthol in the menthol particles is present in the form of L-menthol. (6) The method according to any one of (1) to (5), wherein the menthol content, in particular the L-menthol content, of the menthol particles is greater than 80% by weight, in particular greater than 90% by weight, in particular greater than 99.5% by weight, preferably greater than 99.7% by weight, based on the total weight of the particles. (7) The method according to any one of (1) to (6), wherein menthol particles having a size in the range of 1 to 35 mm, in particular 4 to 35 mm, in particular 5 to 30 mm, preferably 10 to 25 mm, preferably 12 to 24 mm, in particular 15 to 20 mm, are used. (8) The method according to any of (1) to (7), wherein menthol particles in the form of flakes, spheres or pellets, preferably in the form of flakes, are used. (9) The method according to any one of (1) to (8), wherein menthol particles in the form of flakes having a thickness of 0.2 to 15 mm, preferably 4 to 10 mm, in particular 6 to 8 mm, are used. (10) The method according to any of (1) to (9), wherein menthol in the form of flakes is used as the menthol particles obtained by contacting the menthol melt with two spaced apart cooled surfaces, which involves solidification of the menthol melt into menthol, while maintaining contact between the solidifying menthol melt and the cooled surfaces at least until solidification is complete. (11) The method according to (10), wherein 0.1% to 50% by weight, in particular 1% to 40% by weight, in particular 5% to 35% by weight, preferably 10% to 30% by weight of menthol seed crystals are mixed into the menthol melt used before it comes into contact with the cooling surface. (12) The method according to (11), wherein the seed crystals are formed by treatment of the menthol melt used in a scraped surface cooler or in an extruder. (13) The method according to any one of (10) to (12), wherein the two cooling surfaces have a planar parallel orientation and are separated by a distance of 0.2 to 15 mm, preferably 2 to 10 mm, in particular 3 to 9 mm, in particular 5 to 8 mm, in particular 6 to 8 mm. (14) Menthol particles stabilized against caking, obtained by the method according to any one of (1) to (13). (15) Use of menthol particles stabilized against caking according to (14) in the manufacture of daily necessities and consumer goods or in daily necessities and consumer goods. (16) 20 kg of menthol granules are molded and then a) packaged in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, the bag is sealed, and the bag is packaged in a rectangular box made of double-walled corrugated board and having internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; b) the box is stored at 20° C. for 10 days on the side formed by L(box) and H(box), c) This is then dropped once from a height of 1.5 m onto an inelastic surface, in a plane parallel to the sides formed by L(box) and H(box). The storage-stable menthol particles obtained when Storage stability S=[(Z 1 -Z 2 ) / Z 1 ] is 0.25 or less, particularly 0.2 or less, and preferably 0.1 or less, 1 is the number of particles after compaction, and Z 2 is the number of particles after 20 weeks of molding, Menthol particles. (17) The menthol particle according to (16), wherein menthol is present in the form of L-menthol. (18) Menthol particles according to (16) or (17), in which the menthol content, in particular the L-menthol content, is greater than 80% by weight, in particular greater than 90% by weight, in particular greater than 99.5% by weight, preferably greater than 99.7% by weight, based on the total weight of the particles. (19) Menthol particles according to any one of (16) to (18), wherein the menthol particles have a size in the range of 1 to 35 mm, in particular 4 to 35 mm, in particular 5 to 30 mm, preferably 10 to 25 mm, preferably 12 to 24 mm, in particular 15 to 20 mm. (20) The menthol particles according to any one of (16) to (19), wherein the menthol particles are in the form of flakes, spheres or pellets, preferably in the form of flakes. (21) Menthol particles according to any one of (16) to (20), wherein the menthol particles are in the form of flakes having a thickness of 0.2 to 15 mm, preferably 4 to 10 mm, in particular 6 to 8 mm. (22) Menthol particles according to any of (16) to (21), wherein the menthol is used in the form of flakes as menthol particles obtained by contacting a menthol melt with two spaced apart cooled surfaces, which involves solidification of the menthol melt into menthol, while maintaining contact between the solidifying menthol melt and the cooled surfaces at least until solidification is complete. (23) Use of the storage-stable menthol particles according to any of (16) to (22) in the manufacture of daily necessities and consumer goods or in daily necessities and consumer goods.

Claims

1. A method for producing menthol particles stabilized against caking, comprising storing the menthol particles after molding at a temperature between 0 and 30° C. for at least 7 days, after which the menthol particles are stabilized against caking by the addition of a glycerol-based amine, 20 kg of said menthol particles, - packed in a bag made of a polyethylene film having a thickness of 0.12 mm and having dimensions of length L (bag) 660 mm and width W (bag) 690 mm, sealing the bag; - the bags are packed in a rectangular box made of double-walled corrugated board with internal dimensions of length L (box) 385 mm, width W (box) 320 mm and height H (box) 450 mm, and a cardboard thickness of 6 mm; - The box is dropped once from a height of 1.0 m onto an inelastic surface with the plane parallel to the sides formed by L(box) and H(box). imparts at least the same mechanical energy as it would receive if the menthol particles used have an L-menthol content of more than 80% by weight relative to the total weight of said particles, the menthol particles used are in the form of flakes, and the menthol particles in the form of flakes are obtained by contacting a menthol melt with two spaced apart cooled surfaces, which involves solidification of the menthol melt into menthol, while maintaining contact between the solidifying menthol melt and the cooled surfaces at least until solidification is complete; method.

2. 2. The method of claim 1, wherein the number of particles at the end of the method is still at least 50% of the number of particles used at the start of the method.

3. 3. The method according to claim 1 or 2, wherein at least 50% by weight of the menthol particles stabilized against caking are of the same shape as the menthol particles used.

4. 4. The method according to claim 1, wherein at least 50% by weight of the menthol particles stabilized against caking are of the same size as the menthol particles used.

5. 5. The method according to claim 1, wherein the L-menthol content of the menthol particles is greater than 90% by weight, based on the total weight of the particles.

6. 6. The method of claim 5, wherein the L-menthol content of the menthol particles is greater than 99.5% by weight based on the total weight of the particles.

7. 7. The method according to any one of claims 1 to 6, wherein menthol particles having a size in the range of 1 to 35 mm are used.

8. 8. The method according to claim 7, wherein menthol particles having a size in the range of 4 to 35 mm are used.

9. 9. The method according to claim 7 or 8, wherein menthol particles having a size in the range of 10 to 25 mm are used.

10. 10. The method according to any one of claims 1 to 9, wherein menthol particles in the form of flakes having a thickness of 0.2 to 15 mm are used.

11. 11. The method according to claim 10, wherein menthol particles in the form of flakes having a thickness of 4 to 10 mm are used.

12. 12. The method according to any one of claims 1 to 11, wherein 0.1% to 50% by weight of menthol seed crystals are mixed into the menthol melt used before contacting it with the cooling surface.

13. 13. The method according to claim 12, wherein 5% to 35% by weight of menthol seed crystals are mixed into the menthol melt used.

14. 14. The method according to claim 12 or 13, wherein the seed crystals are formed by treatment of the menthol melt used in a scraped surface cooler or in an extruder.

15. 15. The method according to any one of claims 1 to 14, wherein the two cooling surfaces have a planar parallel orientation and are separated by a distance of 0.2 to 15 mm.

16. The method of claim 15, wherein the two cooling surfaces are separated by a distance of 2 to 10 mm.

17. The method according to claim 15 or 16, wherein the two cooling surfaces are separated by a distance of 5 to 8 mm.

Citation Information

Patent Citations

  • Powder containing l-menthol

    JP1996020549A

  • Compressed menthol

    JP2005528436A

  • Menthol-containing solid composition

    JP2008533260A

  • Menthol-containing solid composition

    JP2008534655A

  • spherical menthol particles

    JP2009519992A